Information-Sharing Behaviors Among Sports Fans Using #Hashtags. (August 2021) - Kim, Han Soo; Cho, Kwang Min; Kim, Minjung
The purpose of this study was to explore sports fans' hashtags usage for information sharing over social media on the basis of the theory of interpersonal behavior. We collected data from 323 social media users who have employed hashtags to exchange sports-related information during the past 12 months. The structural equation modeling confirmed affect, perceived usefulness, perceived reciprocity, and social factors as motivators of the intention to share information. Other motivators, including habit and facilitating conditions, function as predictors of actual hashtags posting among sport fans. In deriving empirical evidence and novel insights into the role of hashtags, this research elevated our understanding of information circulation among sport fans over social media and serves as a foundation for inquiries into hashtag adoption in sport domains.